PERBANDINGAN PENERAPAN MODEL TWO STAY TWO STRAY DAN GALLERY WALK TERHADAP AKTIVITAS DAN KEMAMPUAN MENULIS PANTUN SISWA KELAS V GUGUS II KECAMATAN MANGGALA KOTA MAKASSAR - Amin, Nur Azza; Bahri, Aliem; Paida, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine whether there is a difference between the Two Stay Two Stray learning model and the Gallery Walk learning model on students' activities and abilities in writing pantun. The research approach uses a quantitative approach with the type of research used is quasi-experimental. The population of the study was all fifth grade students of Cluster II, Manggala District, Makassar City, consisting of seven schools with a total of 339 students. The research sample selected was fifth grade students of SD Inpres Antang totaling 54 people using the cluster random sampling technique. The data collection technique in the study was carried out through a test technique to determine the activities and abilities of students writing pantun. Based on the descriptive analysis of the results of the study, the average value of student learning activities through the Two Stay Two Stray learning model was 91.13 and through the Gallery Walk learning model was 90.17. The ability to write pantun students in the application of the Two Stay Two Stray learning model obtained an average value of 91.47 and through the Gallery Walk learning model with an average of 90.23. From the results of the analysis of the hypothesis of student learning activities, it was found that there was a significant difference through the application of the Two Stay Two Stray learning model and the Gallery Walk learning model with a significance value of 0.01 <0.05, so it was stated that H0 was rejected and H1 was accepted. While the analysis of the hypothesis of students' ability to write pantun obtained that H0 was accepted and H1 was rejected with a significance value of 0.152 <0.05. So it can be concluded that the Two Stay Two Stray learning model and the Gallery Walk learning model can improve students' ability to write pantun.